The effect of calcium carbonate and calcined clay micro filler materials on the electrical characteristics of polyvinyl chloride for cable insulation - Azmi, Mohd. Asyraf Reduan (2008)
Polyvinyl Chloride (PVC) is widely used as cable insulation for low voltage application. In order to strengthen the electrical properties of the material, some additives have to be added. In this project, various fillers were compounded with PVC. The main parameters that have been studied were dielectric strength, and the dispersion of PVC molecules. The polymer structure of PVC was altered after undergo high voltage stress and it can be related to the breakdown voltage value. The type of fillers that were used in this experiment is Calcium Carbonate NCC-P 1T, Neolite SP, and Calcined Clay. Firstly the density of each test objects was measured using density meter and the value obtained must within the SIRIM specification. Then the dielectric strength test was done under AC stress to observe the breakdown properties. It is observed from the tests that when the density or Specific Gravity (SG) of test sample increased, the breakdown voltage also increased. But after the highest value, the dielectric strength started to show degradation characteristic event though the density is kept increasing. This phenomenon occurred to all formulation of filler materials. The experimental results also show that PVC compounded with 10 wt% of Calcium Carbonate Neolite SP produces the highest breakdown voltage and excellent dispersion. PVC cost also can be reduced by the addition of filler material. The analysis depicted that PVC combined with 10 wt% of CaC03 Neolite SP provides the best profile of cost saving.